PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP STRUKTUR MODAL (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG LISTING DI BEI TAHUN 2011-2014) - Taufiq Andre Kusumo; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2017)
The aim of this research is to analyze the effect of corporate governance to corporate capital structure. Capital is very important in building and ensuring the continuity of the company. The additional capital will be required if the company is doing expantion. Accomplishment of the company's capital can raises agency problems so it’s necessary to make corporate governance. Corporate governance used in this research are boards size, outside directors, institutional ownerships, managerial ownerships and remunerations. This research used annual report of mining companies listed in Indonesia Stock Exchange (IDX) 2011-2014. The sampling method in this research is purposive sampling, the amount of samples are 71 samples. This research used multiple regression analysis data and hypothesis. Result’s show that the board size and remunerations are positively and significant affected to capital structure and outside directors are negatively and significant affected to capital structure. While the other variables such as the intitutional ownerships and managerial ownerships are not significantly affected to capital structure. This research also find that the control variables which are profitability, firm size, and liquidity have significant and negative effect to capital structure.